PENGEMBANGAN SISTEM PENGADUAN MASYARAKAT BERBASIS WEB PADA KANTOR DESA BABAKAN - Siti Nurajizah; Rifa Nurafifah Syabaniah; Fani Nurona Cahya; Elin Panca Saputra; Tiara Iswanti Sudrajat; Widi Intan Priyanti; Balqis Mulia Septiany (INTI Nusa Mandiri, 2026)
The development of information technology encourages village governments to provide public services that are more efficient, transparent, and accessible, including complaint management. In Babakan Village, complaints are still submitted through RT/RW administrators or direct visits to the village office, causing slow responses, difficulties in tracking status, and risks of data loss. This study aims to design and develop SIPEMAS, a web-based public complaint information system that supports online complaint submission, complaint data management, officer responses, and status tracking. The research used the Waterfall software development model consisting of requirement analysis, system design with UML, implementation using PHP with CodeIgniter 3 and MySQL, verification through black-box testing, and maintenance planning. Requirement data were obtained through observation of the existing complaint process, interviews with village officers, and document study. The developed system provides role-based access for citizens and officers, complaint submission with supporting evidence, complaint management, response input, and report recapitulation. Black-box testing on eight main functional scenarios showed valid results for all tested functions (8/8; 100%). A user satisfaction survey showed that 69% of respondents were satisfied with the public complaints system. Therefore, SIPEMAS can support structured complaint management, improve transparency through status tracking, and strengthen the security and documentation of complaint data in Babakan Village.